the effect of managers' decision making styles on success management strategies at Allameh Tabataba'i University - fariba fakhradkhani; Hadi Rezghi Shairsavar (Allameh Tabataba'i University Press, 2017)
The purpose of this study was to investigate the effect of managers' decision making styles on success management strategies at Allameh Tabataba'i University. This research is descriptive-correlative in terms of the type of applied target and data gathering method. The statistical population of this study was all managers (high, middle and executive) of Allameh Tabataba'i University who were employed in the academic year of 1997-96. The sample size was Morgan table to select the sample size and 118 persons were selected based on Morgan's table. In order to collect the views of staff and managers, two questionnaires: Kim's successor (2006), the reliability of which was 0.88 and Bruce & Scott's general decision-making questionnaire, which had a reliability of 0.91 in this research; also for data analysis In order to test the hypotheses, inferential statistics of path analysis and regression analysis were used. The results of the analysis showed that decision-making styles affect successor strategies. The results showed that rational decision making style has a positive and significant relationship with success strategies, as well as intuitive decision making style and lack of meaningfulness with replacement strategies have a non-significant relationship and finally, there is a reverse and meaningful relationship between immediate and avoidant styles